Is Urban Land Development Driven by Economic Development or Fiscal Revenue Stimuli in China?. (September 2018) - Shu, Cheng; Xie, Hualin; Jiang, Jinfa; Chen, Qianru
Highlights: Whether economic factors or fiscal revenue drives urban land development were tested. The difference in the land development intensity in central China is lower than that in eastern and western China. A model of factors influencing urban land development intensity across municipal districts is constructed. Land transfer revenue drives the land development in cities at the municipal or higher levels. Abstract: Since the reform and opening-up, urban land development in China mainland has been increasing dramatically with significant regional differences. Using the panel data of municipal districts in 246 cities at the prefectural or higher levels in Chinese mainland from 2004 to 2014, based on the analysis of the differences in land development intensity in municipal districts, a model of factors affecting land development is built to verify whether the urban land development is driven by economic development or fiscal revenue from the perspectives of economic development and fiscal revenue. The conclusions are as follows: first, the intensity of land development varies significantly among municipal districts. The difference in the intensity of land development increases with the increase of city scale. The difference in the intensity of land development in central China is lower than that in eastern and western China. Second, the primary factors affecting the intensity of urban land development are economic growth, population urbanization, and population density. Finally, land transfer revenues also drive the land development in cities at the prefectural or higher levels to a considerable extent, which is proposed as "land finance" (local governments rely on the sale of land use rights to obtain extra-budgetary income to maintain local fiscal expenditure) in the literature.